Determination of Design Criteria for Floating Portable Toilet Applied at Flood Prone Area - Fatimah, Eldina; Fauzi, Muhammad; Fauzia, Arisna; Kiswanto, Kiswanto; Abdullah, Abdullah; Clara, Bella Fitrah; Syahna, Diyatura (International Journal of Disaster Management, 2023)
Communities living in flood-prone areas generally experience difficulty accessing toilet facilities when the water level fluctuates. Information on providing toilets that can adapt to changes in the water level at disaster sites has yet to be published. In addition, the obstacles often faced in the provision of toilets are difficulty in distribution because they cannot be disassembled, toilets are unstable when placed above the water level, and they are not environmentally friendly. The availability of a comprehensive type of floating portable toilet that is suited for installation in advance (before flooding) and adapts to floating conditions should be more investigated. This research aims to select critical criteria for floating portable toilet design. Interpretive Structural Modelling (ISM) is used to determine the most essential Criteria (P). Secondary data collected include information related to toilet design that has been carried out in various countries, and primary data is collected by distributing questionnaires to as many as 22 selected key respondents. The results showed that the critical factors in designing a floating portable toilet were classified into 6 (six) important parameters, namely: Design and Environmental Management System, Safety, Cleanliness, Amenities, and facilities, Ease of Mobility, and Length of construction time.